A high-strength and high-toughness TiZrNbV series high-entropy alloy with ordered oxygen complex and preparation method thereof

By performing low-temperature heat treatment in high-entropy alloys, the binding of Zr-M elements and the diffusion of oxygen atoms are promoted to form an ordered oxygen composite structure, which solves the problem that existing high-entropy alloys are difficult to form an ordered oxygen composite when the cooling rate is slow, and achieves the improvement of high strength and high toughness.

CN116770150BActive Publication Date: 2025-04-25BEIJING INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310717091.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2025-04-25
Estimated Expiration
2043-06-16

AI Technical Summary

Technical Problem

The existing high-entropy alloys have slow cooling rates in larger-sized engineering structural parts, making it difficult to form ordered oxygen composites, limiting their engineering applications.

Method used

The element diffusion rate is increased through low-temperature heat treatment, the binding of Zr-M elements is promoted, and the Zr-M-O ​​ordered oxygen composite structure is formed through the diffusion of oxygen atoms, thereby enhancing the strength and plasticity of the alloy.

Benefits of technology

The strong plasticity improvement of large-size oxygen-containing high-entropy alloys is achieved, and the method is simple, safe, reliable, economical and practical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116770150B_ABST
    Figure CN116770150B_ABST
Patent Text Reader

Abstract

The present invention relates to a high-strength and high-toughness TiZrNbV series high-entropy alloy with an ordered oxygen complex and a preparation method thereof, belonging to the technical field of high-entropy alloys. The chemical formula of the high-entropy alloy is Ti a Zr b Nb c V d M e O f , wherein M is one or more of W, Al, Cr, Fe, Mg, Be, Li, Mo, Mn, Co, Ni and Si, 25≤a≤65, 0<b<55, 0<c<35, 0<d≤30, 0<e<20, 0<f≤5, and a+b+c+d+e+f=100, the high entropy alloy is mainly BCC phase, has an ordered oxygen complex M‑Zr‑O, the ordered oxygen complex M‑Zr‑O is disc-shaped, has a diameter of 2-5 nm, and a thickness of less than or equal to 1 nm; the tensile strength of the high entropy alloy is 900-1400 MPa, and the elongation at break is 15%-45%. The present invention further improves the strength and plasticity of the oxygen-containing high entropy alloy by low-temperature heat treatment, has a simple process, and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-strength and high-toughness TiZrNbV series high-entropy alloy with an ordered oxygen complex and a preparation method thereof, belonging to the technical field of high-entropy alloys. Background Art

[0002] In 2004, Ye Junwei formally proposed the concept of high entropy alloy for the first time. It breaks the traditional alloy design concept of single principal component based on mixing enthalpy, and is a new type of multi-principal metal material designed mainly based on configuration entropy. High entropy alloys are generally composed of multiple elements in equiatomic or nearly equiatomic ratios, and tend to form a simple structure with disorder and high concentration solid solution. The introduction of the concept of high entropy alloy also provides a new direction for the development of lightweight alloys. So far, a variety of lightweight high entropy alloys have been reported, which have excellent comprehensive properties such as high strength, high wear resistance, corrosion resistance, and high temperature resistance. They have broad application prospects in high-performance warheads, lightweight armor, aerospace, and nuclear energy.

[0003] With the development of research on lightweight high-entropy alloys, people have begun to focus on regulating the mechanical properties of lightweight high-entropy alloys through more means. In recent years, studies have found (CN 201310690502.7) that by introducing oxygen atoms to form ordered oxygen complexes, strength and plasticity can be improved simultaneously, breaking the curse that metal materials cannot have both strength and plasticity, and providing new ideas for scientific researchers to re-understand interstitial strengthening and ordered strengthening and design high-toughness metal materials. However, current reports show that the ordered oxygen complex can only be formed at an extremely fast cooling rate. For larger-sized engineering structural parts, the cooling rate during smelting and forging is slow, which is not conducive to the formation of ordered oxygen complexes, thus limiting the engineering application of this type of alloy. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a high-strength and high-toughness TiZrNbV series high-entropy alloy with an ordered oxygen complex and a preparation method thereof. The element diffusion rate is increased by low-temperature heat treatment, which promotes the combination of Zr-M elements with large atomic size differences and large electronegativity differences. At the same time, due to the large electronegativity difference and more negative mixing enthalpy, the interstitial atom O is more likely to combine with Zr and M, and the temperature rise causes O to diffuse rapidly into the tetrahedral / octahedral gaps near the Zr-M ordered structure, forming a Zr-MO ordered oxygen complex structure, thereby achieving the improvement of the strength and plasticity of large-size oxygen-containing high-entropy alloys. The method does not require changing the alloy composition and the operation method is simple to operate, safe and reliable, and economical and practical.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows.

[0006] A high-strength and high-toughness TiZrNbV series high-entropy alloy with an ordered oxygen complex, wherein the chemical formula of the high-entropy alloy is Ti a Zr b Nb c V d M e O f , wherein M is one or more of W, Al, Cr, Fe, Mg, Be, Li, Mo, Mn, Co, Ni and Si, 25≤a≤65, 0<b<55, 0<c<35, 0<d≤30, 0<e<20, 0<f≤5, and a+b+c+d+e+f=100, the high entropy alloy is mainly composed of a BCC phase and has an ordered oxygen complex M-Zr-O, the ordered oxygen complex M-Zr-O is disc-shaped, with a diameter of 2-5 nm and a thickness of less than or equal to 1 nm; the tensile strength of the high entropy alloy is 900-1400 MPa, and the elongation at break is 15%-45%.

[0007] Preferably, 35≤a≤55, 5<b<30, 0<c<30, 0<d≤30, 0<e<20, 0<f≤3, and a+b+c+d+e+f=100.

[0008] Preferably, when M is one or more of W, Al, Fe, Mg, Be, Li, Mn, Co, Ni and Si, 0<e≤10.

[0009] Preferably, 0<f≤2.

[0010] Preferably, 40≤a≤50, 10≤b≤20, 10≤c≤20, 5≤d≤15, 2≤e≤10, 1≤f≤2, and a+b+c+d+e+f=100.

[0011] A method for preparing a high-strength and high-toughness TiZrNbV-based high-entropy alloy having an ordered oxygen complex according to the present invention comprises the following steps:

[0012] (1) weighing raw materials according to the atomic ratio of the high entropy alloy and preparing a TiZrNbV series high entropy alloy ingot;

[0013] (2) homogenizing the TiZrNbV high entropy alloy ingot;

[0014] (3) The TiZrNbV high entropy alloy ingot after homogenization treatment is kept at 200-500°C for 8-200 hours and then cooled to obtain a high-strength and high-toughness TiZrNbV high entropy alloy with an ordered oxygen complex.

[0015] Preferably, in step (1), the raw material is a metal element or an alloy, and oxygen is added in the form of oxides TiO2 and / or ZrO2.

[0016] Preferably, in step (1), the TiZrNbV high entropy alloy ingot is prepared by smelting, mechanical alloying or 3D printing. More preferably, the smelting method is induction melting, suspension melting, arc melting or electron beam melting. More preferably, during smelting, TiO2 and / or ZrO2 are first smelted with part of the metal element or alloy to form an intermediate alloy, and then the remaining raw materials are added for smelting, and each alloy is smelted more than twice to obtain the TiZrNbV high entropy alloy ingot.

[0017] Preferably, in step (2), during the homogenization treatment, the temperature is 900-1200° C. and the insulation time is 1-24 h.

[0018] Preferably, in step (3), the temperature is 250-400° C. and the insulation time is 8-24 h.

[0019] Beneficial Effects

[0020] (1) The present invention provides a high-strength and high-toughness TiZrNbV series high-entropy alloy with an ordered oxygen complex, wherein the high-entropy alloy has a disc-shaped ordered oxygen complex M-Zr-O with a specific structural size. On the one hand, this structure has a high bond energy and is not easily destroyed, which effectively improves the strength of the alloy. On the other hand, the disc-shaped structural feature increases the specific surface area of ​​the ordered structure, making it easier to interact with dislocations, hindering the plane slip of dislocations, forcing them to cross-slip, promoting the proliferation and uniform deformation of dislocations, and ultimately improving its plastic deformation capacity.

[0021] (2) The present invention provides a high-strength and high-toughness TiZrNbV series high-entropy alloy with an ordered oxygen complex, wherein the matrix elements in the TiZrNbV series high-entropy alloy have a large solid solubility for oxygen, such as the solid solubility limit of O in β-Ti reaches nearly 6.0 at.%, the solid solubility limit in β-Zr reaches 10.5 at.%, the solid solubility limit in Nb reaches 9.0 at.%, and the solid solubility limit in V reaches 16 at.%, so a large amount of oxygen addition will not produce oxides and reduce the plasticity of the alloy. Further, by adjusting the atomic ratio of each element and selecting the type of M element, a high-entropy alloy with higher strength and plasticity can be obtained.

[0022] (3) The present invention provides a method for preparing a high-strength and high-toughness TiZrNbV series high-entropy alloy with an ordered oxygen complex. During the low-temperature heat treatment process, since the diffusion activation energy of O (oxygen) is much smaller than that of other metals, O can diffuse faster than other metal elements. At the same time, since the three elements O, M, and Zr in the TiZrNbVMO series high-entropy alloy have large atomic radius differences and electronegativity differences, the three elements are very easy to combine, among which M-Zr forms a local ordered structure of the B2 structure, and O occupies the tetrahedron / octahedron gap of the B2 ordered structure. On the one hand, this improves the thermal stability of the ordered structure. On the other hand, this occupation of O makes the ordered structure a disk: the diameter of the structure is 2~5 nm, and the thickness is less than 1 nm. Finally, a disk-shaped ordered oxygen complex of M-Zr-O is formed.

[0023] (4) The present invention provides a method for preparing a high-strength and high-toughness TiZrNbV series high-entropy alloy with an ordered oxygen complex. The low-temperature heat treatment temperature is 200-500°C, which is lower than the precipitation temperature of the intermetallic compound of the system. Too low a temperature is not conducive to the diffusion of O atoms and it is difficult to form an ordered oxygen complex structure. Too high a temperature will destroy the ordered oxygen complex. At the same time, too high a temperature will cause the alloy grain size to grow and reduce the strength and plasticity of the high-entropy alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Transmission electron microscope (TEM) images of the high entropy alloys prepared in Example 1 and Comparative Example 1.

[0025] Figure 2 1 and 2 are X-ray diffraction (XRD) patterns of the high entropy alloys prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below with reference to specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.

[0027] In the following examples and comparative examples:

[0028] The purity of the metal elements Ti, Zr and M is greater than 99 wt%, the purity of Nb and V is greater than 99 wt%, and oxygen is added in the form of TiO2 or ZrO2.

[0029] TEM sample preparation and observation: The sample was cut into 10×10×0.3 mm thick slices by wire cutting, and the slices were polished to less than 40 μm thickness using metallographic sandpaper and punched into 3 mm diameter discs. The TEM sample was prepared by ion thinning, and the crystal structure of the alloy and the presence of precipitated phase were observed along the

[011] direction under a TEM.

[0030] Density test: Use wire cutting to cut the sample into 10×10×10 mm square blocks, use metallographic sandpaper to polish the sample surface, and finally clean the polished blocks with alcohol. Then use an electronic balance to test the density of the alloy using the Archimedean density method.

[0031] Mechanical properties test: A CMT4305 microcomputer electronic universal testing machine was used to conduct axial quasi-static tensile tests at room temperature, with a strain rate of 1×10 -3 s -1 The test specimen is a non-standard I-shaped piece with a thickness of 1.0 mm, a width of 3.14 mm, a parallel section length of 10 mm, and a gauge length of 5 mm. The high entropy alloy to be tested is prepared into a specimen of the required size using a wire cutting device, and then the surface of the specimen is polished clean with 120#, 400#, 800#, and 1200# sandpaper in turn, and then a room temperature tensile test is performed using a universal electronic testing machine to obtain the stress-strain curve of the high entropy alloy.

[0032] Phase analysis: The X-ray diffraction spectrum of the high entropy alloy was measured using a Rigaku Smartlab X-ray diffractometer from Japan. The instrument has a scanning angle range of 20° to 100°, uses Cu target Kα rays, has an operating voltage of 40kV, an operating current of 110mA, a scanning speed of 6° / min, a step length of 0.02°, and a measurement angle error of less than 0.01°.

[0033] Example 1

[0034] (1) Using metal single substances Ti, Zr, Al, Nb, and V as raw materials, they were first polished with a grinding wheel to remove the oxide film on the surface of the raw materials, then placed in anhydrous alcohol for ultrasonic cleaning and drying, and then weighed according to the atomic ratio of Ti: Zr: Nb: V: Al: O = 49.50: 19.80: 14.85: 9.90: 4.95: 1.00. Then, 50 g of pure Ti and TiO2 were placed in a vacuum arc melting furnace, and the sample was evacuated. When the vacuum degree reached 2.5×10 -3 After Pa, fill the furnace chamber with argon gas to 0.05MPa, and then start smelting to melt TiO2 and pure Ti into an intermediate alloy for standby use;

[0035] (2) The remaining metal raw materials and the master alloy in step 1 are placed in a crucible in an induction melting furnace, and the vacuum degree in the furnace is reduced to less than 5×10 -3 Pa, and then fill the furnace with argon gas until the pressure reaches 0.05 MPa, then carry out smelting, and keep the temperature for 2 min after the raw materials are completely melted to make the molten alloy liquid evenly mixed, and then turn off the power of the induction melting furnace after the heat preservation to cool and obtain the ingot;

[0036] (3) After the ingot is turned over, it is smelted again according to the conditions of step (2). The smelting is repeated twice to obtain a density of 5.63 g / cm 3 Ti 49.50 Zr 19.80 Nb 14.85 V 9.90 Al 4.95 O 1.00 High entropy alloy.

[0037] (4) The alloy was cut into a size of 10 × 10 × 30 mm using wire-cut electrospark cutting. The surface oxides and oil stains were polished clean with sandpaper. The polished alloy was then cleaned with industrial alcohol in an ultrasonic bath and vacuum sealed with a quartz tube. Subsequently, a homogenization treatment was performed at 1000 °C / 2 h, followed by a low-temperature aging heat treatment of X °C / Y h (X = 300, 400, 500, Y = 8, 24, 72, 168).

[0038] The high entropy alloy prepared in this embodiment was subjected to TEM test. Figure 1 From the TEM images of homogenization treatment +300℃ / 24h and solution treatment +400℃ / 24h, it can be seen that the high entropy alloy is a single-phase BCC structure without the presence of precipitated phase. At the same time, according to the selected electron diffraction, it can be seen that an ordered oxygen structure appears in the alloy, and the diameter of the disc-shaped ordered oxygen structure is 2~5 nm, and the thickness is less than or equal to 1 nm.

[0039] The high entropy alloy prepared in this embodiment was subjected to XRD test. Figure 1 It can be seen from the XRD spectrum in that, compared with the high entropy alloy without adding O prepared in Comparative Example 1, the high entropy alloy containing O prepared in this embodiment still maintains a BCC single-phase structure, and no characteristic peak of the second phase appears.

[0040] The mechanical properties of the high entropy alloy prepared in this embodiment were tested. Compared with the high entropy alloy prepared in Comparative Example 1 without low temperature aging, the strength of the high entropy alloy prepared in this embodiment with low temperature aging was improved and the fracture strain was greatly improved. The specific results are shown in Table 1.

[0041] Table 1

[0042]

[0043] Example 2

[0044] (1) Using metal single substances Ti, Zr, Al, Nb, and V as raw materials, first grind with a grinding wheel to remove the oxide film on the surface of the raw materials, then place them in anhydrous alcohol for ultrasonic vibration cleaning and dry, and then weigh each metal single substance and TiO2 particles according to the atomic ratio of Ti: Zr: Nb: V: Al: O = 49.25: 19.70: 14.78: 9.85: 4.92: 1.50. Then, put 50 g of pure Ti and TiO2 into a vacuum arc melting furnace, evacuate the sample, and when the vacuum degree reaches 2.5×10 -3 After Pa, argon gas is filled into the furnace chamber to 0.05 MPa, and then smelting is started to melt TiO2 and pure Ti into an intermediate alloy for standby use;

[0045] (2) The remaining metal raw materials and the master alloy in step 1 are placed in a crucible in an induction melting furnace, and the vacuum degree in the furnace is then reduced to less than 5×10 -3 Pa, and then fill the furnace with argon gas until the pressure reaches 0.05 MPa, then carry out smelting, and keep the temperature for 2 min after the raw materials are completely melted to make the molten alloy liquid evenly mixed, and then turn off the power of the induction melting furnace after the heat preservation to cool and obtain the ingot;

[0046] (3) After the ingot is turned over, the smelting is repeated according to the conditions of step (2). The smelting is repeated twice to obtain a density of 5.62 g / cm 3 Ti 49.25 Zr 19.70 Nb 14.78 V 9.85 Al 4.92 O 1.50 High entropy alloy.

[0047] (4) The alloy was cut into a size of 10 × 10 × 30 mm using wire electrospark cutting. The surface oxides and oil stains were polished clean with sandpaper. The polished alloy was then cleaned with industrial alcohol in an ultrasonic bath and vacuum sealed with a quartz tube. Subsequently, a homogenization treatment was performed at 1000 °C for 6 h, followed by a low-temperature aging heat treatment of X °C for Y h (X = 300, 400, 500, Y = 8, 24, 72).

[0048] The high entropy alloy prepared in this embodiment was subjected to TEM testing. The results showed that the high entropy alloy had a single-phase BCC structure without the presence of a precipitated phase. At the same time, according to selected electron diffraction, an ordered oxygen structure appeared in the alloy. The diameter of the disc-shaped ordered oxygen structure was 2 to 5 nm, and the thickness was less than or equal to 1 nm.

[0049] The mechanical properties of the high entropy alloy prepared in this embodiment were tested. Compared with the high entropy alloy prepared in Comparative Example 1 without low temperature aging, the strength of the high entropy alloy prepared in this embodiment with low temperature aging was improved and the fracture strain was greatly improved. The specific results are shown in Table 2.

[0050] Table 2

[0051]

[0052] Example 3

[0053] (1) Using metal single substances Ti, Zr, Al, Nb, and V as raw materials, first grind with a grinding wheel to remove the oxide film on the surface of the raw materials, then place them in anhydrous alcohol for ultrasonic vibration cleaning and dry, and then weigh each metal single substance and TiO2 particles according to the atomic ratio of Ti: Zr: Nb: V: Al: O = 39.60: 19.80: 19.80: 14.85: 4.95: 1.00. Then, put 50 g of pure Ti and TiO2 into a vacuum arc melting furnace, evacuate the sample, and when the vacuum degree reaches 2.5×10 -3 After Pa, argon gas is filled into the furnace chamber to 0.05 MPa, and then smelting is started to melt TiO2 and pure Ti into an intermediate alloy for standby use;

[0054] (2) The remaining metal raw materials and the master alloy in step 1 are placed in a crucible in an induction melting furnace, and the vacuum degree in the furnace is then reduced to less than 5×10 -3 Pa, and then fill the furnace with argon gas until the pressure reaches 0.05 MPa, then carry out smelting, and keep the temperature for 2 min after the raw materials are completely melted to make the molten alloy liquid evenly mixed, and then turn off the power of the induction melting furnace after the heat preservation to cool and obtain the ingot;

[0055] (3) After the ingot is turned over, the smelting is repeated according to the conditions of step (2). The smelting is repeated twice to obtain a density of 5.92 g / cm 3 Ti 39.60 Zr 19.80 Nb 19.80 V 14.85 Al 4.95 O 1.00 High entropy alloy.

[0056] (4) The alloy was cut into a size of 10 × 10 × 30 mm using wire electrospark cutting. The surface oxides and oil stains were polished clean with sandpaper. The polished alloy was then cleaned with industrial alcohol in an ultrasonic bath and vacuum sealed with a quartz tube. Subsequently, a homogenization treatment was performed at 1000 °C for 4 h, followed by a low-temperature aging heat treatment of X °C for Y h (X = 300, 400, 500, Y = 8, 24, 72, 168).

[0057] The high entropy alloy prepared in this embodiment was subjected to TEM testing. The results showed that the high entropy alloy had a single-phase BCC structure without the presence of a precipitated phase. At the same time, according to selected electron diffraction, an ordered oxygen structure appeared in the alloy. The diameter of the disc-shaped ordered oxygen structure was 2 to 5 nm, and the thickness was less than or equal to 1 nm.

[0058] The mechanical properties of the high entropy alloy prepared in this embodiment were tested. Compared with the high entropy alloy prepared in Comparative Example 2 without low temperature aging, the strength of the high entropy alloy prepared in this embodiment with low temperature aging was improved and the fracture strain was greatly improved. The specific results are shown in Table 3.

[0059] Table 3

[0060]

[0061] Example 4

[0062] (1) Using metal single substances Ti, Zr, Al, Nb, and V as raw materials, first grind with a grinding wheel to remove the oxide film on the surface of the raw materials, then place them in anhydrous alcohol for ultrasonic vibration cleaning and dry, and then weigh each metal single substance and TiO2 particles according to the atomic ratio of Ti: Zr: Nb: V: Al: O = 39.60: 34.65: 9.90: 9.90: 4.95: 1.00. Then, put 50 g of pure Ti and TiO2 into a vacuum arc melting furnace, evacuate the sample, and when the vacuum degree reaches 2.5×10 -3 After Pa, argon gas is filled into the furnace chamber to 0.05 MPa, and then smelting is started to melt TiO2 and pure Ti into an intermediate alloy for standby use;

[0063] (2) The remaining metal raw materials and the master alloy in step 1 are placed in a crucible in an induction melting furnace, and the vacuum degree in the furnace is then reduced to less than 5×10 -3 Pa, and then fill the furnace with argon gas until the pressure reaches 0.05 MPa, then carry out smelting, and keep the temperature for 2 min after the raw materials are completely melted to make the molten alloy liquid evenly mixed, and then turn off the power of the induction melting furnace after the heat preservation to cool and obtain the ingot;

[0064] (3) After the ingot is turned over, the smelting is repeated according to the conditions of step (2). The smelting is repeated twice to obtain a density of 5.77 g / cm 3 Ti 39.60 Zr 34.65 Nb 9.90 V 9.90 Al 4.95 O 1.00 High entropy alloy.

[0065] (4) The alloy was cut into a size of 10 × 10 × 30 mm using wire electrospark cutting. The surface oxides and oil stains were polished clean with sandpaper. The polished alloy was then cleaned with industrial alcohol in an ultrasonic bath and vacuum sealed with a quartz tube. Subsequently, a homogenization treatment was performed at 1000 °C / 2 h, and then a low-temperature aging heat treatment was performed at X °C / Y h (X = 300, 400, 500, Y = 8, 24, 72).

[0066] The high entropy alloy prepared in this embodiment was subjected to TEM testing. The results showed that the high entropy alloy had a single-phase BCC structure without the presence of a precipitated phase. At the same time, according to selected electron diffraction, an ordered oxygen structure appeared in the alloy. The diameter of the disc-shaped ordered oxygen structure was 2 to 5 nm, and the thickness was less than or equal to 1 nm.

[0067] The mechanical properties of the high entropy alloy prepared in this embodiment were tested. Compared with the high entropy alloy prepared in Comparative Example 1 without low temperature aging, the strength of the high entropy alloy prepared in this embodiment with low temperature aging was improved and the fracture strain was greatly improved. The specific results are shown in Table 4.

[0068] Table 4

[0069]

[0070] Example 5

[0071] (1) Using metal single substances Ti, Zr, Mo, Nb, and V as raw materials, first grind with a grinding wheel to remove the oxide film on the surface of the raw materials, then place them in anhydrous alcohol for ultrasonic vibration cleaning and dry, and then weigh each metal single substance and TiO2 particles according to the atomic ratio of Ti: Zr: Nb: V: Mo: O = 49.50: 19.80: 14.85: 9.90: 4.95: 1.00. Then, put 50 g of pure Ti and TiO2 into a vacuum arc melting furnace, evacuate the sample, and when the vacuum degree reaches 2.5×10 -3 After Pa, argon gas is filled into the furnace chamber to 0.05 MPa, and then smelting is started to melt TiO2 and pure Ti into an intermediate alloy for standby use;

[0072] (2) The remaining metal raw materials and the master alloy in step 1 are placed in a crucible in an induction melting furnace, and the vacuum degree in the furnace is then reduced to less than 5×10 -3 Pa, and then fill the furnace with argon gas until the pressure reaches 0.05 MPa, then carry out smelting, and keep the temperature for 2 min after the raw materials are completely melted to make the molten alloy liquid evenly mixed, and then turn off the power of the induction melting furnace after the heat preservation to cool and obtain the ingot;

[0073] (3) After the ingot is turned over, it is smelted again according to the conditions of step (2). The smelting is repeated twice to obtain a density of 5.95 g / cm 3 Ti 49.50 Zr 19.80 Nb 14.85 V 9.90 Mo 4.95 O 1.00 High entropy alloy.

[0074] (4) The alloy was cut into a size of 10 × 10 × 30 mm using wire electrospark cutting. The surface oxides and oil stains were polished clean with sandpaper. The polished alloy was then cleaned with industrial alcohol in an ultrasonic bath and vacuum sealed with a quartz tube. Subsequently, a homogenization treatment was performed at 1000 °C for 8 h, followed by a low-temperature aging heat treatment of X °C for Y h (X = 300, 400, 500, Y = 8, 24, 72).

[0075] The high entropy alloy prepared in this embodiment was subjected to TEM testing. The results showed that the high entropy alloy had a single-phase BCC structure without the presence of a precipitated phase. At the same time, according to selected electron diffraction, an ordered oxygen structure appeared in the alloy. The diameter of the disc-shaped ordered oxygen structure was 2 to 5 nm, and the thickness was less than or equal to 1 nm.

[0076] The mechanical properties of the high entropy alloy prepared in this embodiment were tested. Compared with the high entropy alloy prepared in Comparative Example 4 without low temperature aging, the strength of the high entropy alloy prepared in this embodiment with low temperature aging was improved and the fracture strain was greatly improved. The specific results are shown in Table 5.

[0077] Table 5

[0078]

[0079] Example 6

[0080] (1) Using metal single substances Ti, Zr, Al, Nb, V, and Mo as raw materials, they were first polished with a grinding wheel to remove the oxide film on the surface of the raw materials, then placed in anhydrous alcohol for ultrasonic vibration cleaning and drying, and then weighed each metal single substance and TiO2 particles according to the atomic ratio of Ti: Zr: Nb: V: Al: Mo: O = 46.78: 18.71: 14.03: 9.36: 4.68: 5.44: 1.00. Then, 50 g of pure Ti and TiO2 were placed in a vacuum arc melting furnace, and the sample was evacuated. When the vacuum degree reached 2.5×10 -3 After Pa, argon gas is filled into the furnace chamber to 0.05 MPa, and then smelting is started to melt TiO2 and pure Ti into an intermediate alloy for standby use;

[0081] (2) The remaining metal raw materials and the master alloy in step 1 are placed in a crucible in an induction melting furnace, and the vacuum degree in the furnace is then reduced to less than 5×10 -3 Pa, and then fill the furnace with argon gas until the pressure reaches 0.05 MPa, then carry out smelting, and keep the temperature for 2 min after the raw materials are completely melted to make the molten alloy liquid evenly mixed, and then turn off the power of the induction melting furnace after the heat preservation to cool and obtain the ingot;

[0082] (3) After the ingot is turned over, the smelting is repeated according to the conditions of step (2). The smelting is repeated twice to obtain a density of 5.83 g / cm 3 Ti 46.78 Zr 18.71 Nb 14.03 V 9.36 Al 4.68 Mo 5.44 O 1.00 High entropy alloy.

[0083] (4) The alloy was cut into a size of 10 × 10 × 30 mm using wire electrospark cutting. The surface oxides and oil stains were polished clean with sandpaper. The polished alloy was then cleaned with industrial alcohol in an ultrasonic bath and vacuum sealed with a quartz tube. Subsequently, a homogenization treatment was performed at 1000 °C / 8 h, followed by a low-temperature aging heat treatment of X °C / Y h (X = 300, 400, Y = 8, 24, 72).

[0084] The high entropy alloy prepared in this embodiment was subjected to TEM testing. The results showed that the high entropy alloy had a single-phase BCC structure without the presence of a precipitated phase. At the same time, according to selected electron diffraction, an ordered oxygen structure appeared in the alloy. The diameter of the disc-shaped ordered oxygen structure was 2 to 5 nm, and the thickness was less than or equal to 1 nm.

[0085] The mechanical properties of the high entropy alloy prepared in this embodiment were tested. Compared with the high entropy alloy prepared in Comparative Example 5 without low temperature aging, the strength of the high entropy alloy prepared in this embodiment with low temperature aging was improved and the fracture strain was greatly improved. The specific results are shown in Table 6.

[0086] Table 6

[0087]

[0088] Example 7

[0089] (1) Using metal single substances Ti, Zr, Al, Nb, V, and W as raw materials, first grind with a grinding wheel to remove the oxide film on the surface of the raw materials, then place them in anhydrous alcohol for ultrasonic vibration cleaning and dry, and then weigh each metal single substance and TiO2 particles according to the atomic ratio of Ti: Zr: Nb: V: Al: W: O = 47.52: 19.01: 14.26: 9.50: 4.75: 3.96: 1.00. Then, put 50 g of pure Ti and TiO2 into a vacuum arc melting furnace, evacuate the sample, and when the vacuum degree reaches 2.5×10 -3 After Pa, argon gas is filled into the furnace chamber to 0.05 MPa, and then smelting is started to melt TiO2 and pure Ti into an intermediate alloy for standby use;

[0090] (2) The remaining metal raw materials and the master alloy in step 1 are placed in a crucible in an induction melting furnace, and the vacuum degree in the furnace is then reduced to less than 5×10 -3 Pa, and then fill the furnace with argon gas until the pressure reaches 0.05 MPa, then carry out smelting, and keep the temperature for 2 min after the raw materials are completely melted to make the molten alloy liquid evenly mixed, and then turn off the power of the induction melting furnace after the heat preservation to cool and obtain the ingot;

[0091] (3) After the ingot is turned over, the smelting is repeated according to the conditions of step (2). The smelting is repeated twice to obtain a density of 6.10 g / cm 3 Ti 47.52 Zr 19.01 Nb 14.26 V 9.50 Al 4.75 W 3.96 O 1.00 High entropy alloy.

[0092] (4) The alloy was cut into a size of 10 × 10 × 30 mm using wire-cut electrospark cutting. The surface oxides and oil stains were polished clean with sandpaper. The polished alloy was then cleaned with industrial alcohol in an ultrasonic bath and vacuum sealed with a quartz tube. Subsequently, a homogenization treatment was performed at 1000 °C / 24 h, followed by a low-temperature aging heat treatment of X °C / Y h (X = 300, 400, Y = 8, 24, 72).

[0093] The high entropy alloy prepared in this embodiment was subjected to TEM testing. The results showed that the high entropy alloy had a single-phase BCC structure without the presence of a precipitated phase. At the same time, according to selected electron diffraction, an ordered oxygen structure appeared in the alloy. The diameter of the disc-shaped ordered oxygen structure was 2 to 5 nm, and the thickness was less than or equal to 1 nm.

[0094] The mechanical properties of the high entropy alloy prepared in this embodiment were tested. Compared with the high entropy alloy prepared in Comparative Example 6 without low temperature aging, the strength of the high entropy alloy prepared in this embodiment with low temperature aging was improved and the fracture strain was greatly improved. The specific results are shown in Table 2.

[0095] Table 7

[0096]

[0097] Example 8

[0098] (1) Using metal single substances Ti, Zr, Al, Nb, V, and W as raw materials, first grind with a grinding wheel to remove the oxide film on the surface of the raw materials, then place them in anhydrous alcohol for ultrasonic vibration cleaning and dry, and then weigh each metal single substance and TiO2 particles according to the atomic ratio of Ti: Zr: Nb: V: Mn: O = 49.50: 19.80: 14.85: 9.90: 4.95: 1.00. Then, put 50 g of pure Ti and TiO2 into a vacuum arc melting furnace, evacuate the sample, and when the vacuum degree reaches 2.5×10 -3 After Pa, argon gas is filled into the furnace chamber to 0.05 MPa, and then smelting is started to melt TiO2 and pure Ti into an intermediate alloy for standby use;

[0099] (2) The remaining metal raw materials and the master alloy in step 1 are placed in a crucible in an induction melting furnace, and the vacuum degree in the furnace is then reduced to less than 5×10 -3 Pa, and then fill the furnace with argon gas until the pressure reaches 0.05 MPa, then carry out smelting, and keep the temperature for 2 min after the raw materials are completely melted to make the molten alloy liquid evenly mixed, and then turn off the power of the induction melting furnace after the heat preservation to cool and obtain the ingot;

[0100] (3) After the ingot is turned over, it is smelted again according to the conditions of step (2). The smelting is repeated twice to obtain a density of 5.82 g / cm 3 Ti 49.50 Zr 19.80 Nb 14.85 V 9.90 Mn 4.95 O 1.00 High entropy alloy.

[0101] (4) The alloy was cut into a size of 10 × 10 × 30 mm using wire-cut electrospark cutting. The surface oxides and oil stains were polished clean with sandpaper. The polished alloy was then cleaned with industrial alcohol in an ultrasonic bath and vacuum sealed with a quartz tube. Subsequently, a homogenization treatment was performed at 1000 °C / 12 h, followed by a low-temperature aging heat treatment of X °C / Y h (X = 300, 400, Y = 8, 24, 72).

[0102] The high entropy alloy prepared in this embodiment was subjected to TEM testing. The results showed that the high entropy alloy had a single-phase BCC structure without the presence of a precipitated phase. At the same time, according to selected electron diffraction, an ordered oxygen structure appeared in the alloy. The diameter of the disc-shaped ordered oxygen structure was 2 to 5 nm, and the thickness was less than or equal to 1 nm.

[0103] The mechanical properties of the high entropy alloy prepared in this embodiment were tested. Compared with the high entropy alloy prepared in Comparative Example 7 without low temperature aging, the strength of the high entropy alloy prepared in this embodiment with low temperature aging was improved and the fracture strain was greatly improved. The specific results are shown in Table 8.

[0104] Table 8

[0105]

[0106] Comparative Example 1

[0107] In this comparative example, low temperature heat treatment is not performed, and the rest is the same as in Example 1.

[0108] Comparative Example 2

[0109] In this comparative example, low temperature heat treatment is not performed, and the rest is the same as in Example 3.

[0110] Comparative Example 3

[0111] In this comparative example, low temperature heat treatment is not performed, and the rest is the same as in Example 4.

[0112] Comparative Example 4

[0113] In this comparative example, low temperature heat treatment is not performed, and the rest is the same as in Example 5.

[0114] Comparative Example 5

[0115] In this comparative example, low-temperature heat treatment is not performed, and the rest is the same as in Example 6.

[0116] Comparative Example 6

[0117] In this comparative example, low-temperature heat treatment is not performed, and the rest is the same as in Example 7.

[0118] Comparative Example 7

[0119] In this comparative example, low-temperature heat treatment is not performed, and the rest is the same as in Example 8.

[0120] The mechanical property test results of the high entropy alloys prepared in Comparative Examples 1-7 are shown in Table 9.

[0121] Table 9

[0122]

[0123] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.

Claims

1. A high-strength and high-toughness TiZrNbV-based high-entropy alloy with an ordered oxygen complex, characterized in that: The chemical formula of the high entropy alloy is recorded as Ti according to the atomic ratio a Zr b Nb c V d M e O f , wherein M is one or more of W, Al, Cr, Fe, Mg, Be, Li, Mo, Mn, Co, Ni and Si, 40≤a≤50, 10≤b≤20, 10≤c≤20, 5≤d≤15, 2≤e≤10, 1≤f≤2, and a+b+c+d+e+f=100, the high entropy alloy is mainly BCC phase, and has an ordered oxygen complex M-Zr-O, the ordered oxygen complex M-Zr-O is disc-shaped, with a diameter of 2-5 nm and a thickness of less than or equal to 1 nm; the tensile strength of the high entropy alloy is 900-1400 MPa, and the elongation at break is 15%-45%; The high entropy alloy is prepared by the following method, which comprises the following steps: (1) weighing raw materials according to the atomic ratio of the high entropy alloy and preparing a TiZrNbV series high entropy alloy ingot; (2) homogenizing the TiZrNbV high entropy alloy ingot; (3) The TiZrNbV high entropy alloy ingot after homogenization treatment is kept at 200-500°C for 8-200 hours and then cooled to obtain a high-strength and high-toughness TiZrNbV high entropy alloy with an ordered oxygen complex.

2. A high-strength and high-toughness TiZrNbV-based high-entropy alloy with an ordered oxygen complex as claimed in claim 1, characterized in that: In step (1), the raw material is a metal element or an alloy, and oxygen is added in the form of oxides TiO2 and / or ZrO2; the TiZrNbV high entropy alloy ingot is prepared by smelting, mechanical alloying or 3D printing.

3. A high-strength and high-toughness TiZrNbV-based high-entropy alloy with an ordered oxygen complex as claimed in claim 2, characterized in that: The smelting method is induction melting, suspension melting, arc melting or electron beam melting. During melting, TiO2 and / or ZrO2 are firstly melted with part of metal elements or alloys to form an intermediate alloy, and then the remaining raw materials are added for melting. Each alloy is melted more than twice to obtain the TiZrNbV series high entropy alloy ingot.

4. A high-strength and high-toughness TiZrNbV-based high-entropy alloy with an ordered oxygen complex as claimed in claim 1, characterized in that: In step (2), during the homogenization treatment, the temperature is 900-1200° C. and the insulation time is 1-24 h.

5. The high-strength and high-toughness TiZrNbV-based high-entropy alloy with ordered oxygen complex according to claim 1, characterized in that: In step (3), the temperature is 250-400°C and the insulation time is 8-24h.

Citation Information

Patent Citations

  • A kind of oxygen strengthened tizrnbhfo high entropy alloy and preparation method thereof

    CN103710607B

  • High-specific-strength high-plasticity refractory high-entropy alloy and preparing method thereof

    CN108677077A

  • Lightweight high-strength refractory high-entropy alloy with high exothermic enthalpy

    CN113652596A